INTERACTION OF TIME-USE AND ACTIVITY TRAVEL PARTICIPATION ON THE PHYSICAL AND SOCIAL HEALTH OF TRAVELERS - ALI, MUJAHID (2021)
Using multi-dimensional three-weeks household time-use and activity diary, this study investigates the interaction between time-use and activity travel participation, built